The Determinants of Capital Structure: An Empirical Investigation into UK Firms - Li, Xuefei (2013)
This paper examines the effects of seven determinants (company size, profitability, tangibility, growth opportunity, non-debt tax shield, effective tax rate, industry impact) on capital structure decisions of UK companies and considers which one of the main theories is more appropriate to explain the leverage choices of UK firms. The dataset contains 200 UK firms selected from FTSE 350 Index including nine industries across a nine-year period from 2004-2012. The industry effects are tested by ANOVA model and other six determinants are handled as panel data and have been investigated by applying Fixed Effect Model (FEM) for total leverage and long-term leverage and Random Effect Model (REM) for short-term leverage respectively. According to our results, this paper claims the pecking order theory fits into our empirical results best. However, the short-term leverage model fails to show any significance on the determinants while only two of the determinants display strong explanatory power on the total and long-term leverage model. This may caused by various limitations of our research. Therefore, further investigation should be conducted in the future.